Development of a portable lab-on-a-valve device for making primary diagnoses based on gold-nanoparticle aggregation induced by a switchable linker. Issue 52 (24th August 2020) - Hahn, Jungwoo; Kim, Eunghee; Han, Hyebin; Choi, Young Jin
Abstract : We have developed a low-cost, portable lab-on-a-valve (LOV) integrated microdevice for the detection of pathogens in primary-diagnosis settings. Abstract : We have developed a low-cost, portable lab-on-a-valve (LOV) integrated microdevice for the detection of pathogens in primary-diagnosis settings. This system was designed for field-based pathogen detection based on the aggregation of gold nanoparticles induced by a switchable linker. A three-way valve, which has attracted much attention as a functional mesofluidic platform for pressure-driven flow, has been designed as a universal reaction platform that combines the functions of fluid flow and a reaction chamber. In addition, we obtain rapid and enhanced visual signals by the use of a syringe filter to remove gold nano-aggregates (Au NAs). Using this device, Salmonella Typhimurium down to 10 1 CFU mL −1 can be visually detected within 30 min by performing a simple operation that requires no complex equipment. This prototype device has great potential for use in the semi-quantitative and qualitative identification of pathogens in on-site primary diagnoses.